Tax Revenue and Infrastructural Development in Nigeria - Lawrence Imeokparia; Ikenna Theodore Nnoli; David Ojo; Olufunmilayo Ajibola (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2025)
This study examines the relationship between tax revenue and infrastructural development in Nigeria. The study explores Company Income Tax (CIT) and Value Added Tax (VAT) as indicators for tax revenue. Also, three measures of capital expenditure; administrative capital expenditure, economic capital expenditure, and social services capital expenditure were adopted as a proxy for infrastructural development. The data used in the study were gathered from 2011-2021 and sourced from the Federal Inland Revenue Service (FIRS) and Central Bank of Nigeria Statistical Bulletin. To establish the relationship between tax revenue and infrastructure development, Pearson correlation and regression analysis were explored. The study finds that there is a positive relationship between CIT and economic capital expenditure, administrative capital expenditure and services capital expenditure. Likewise, the study shows a positive link between VAT and services capital expenditure, economic capital expenditure, and administrative capital expenditure in Nigeria. Therefore, it is recommended that the federal government effectively utilize the revenue generated from tax for infrastructural advancement and ensure there is no wastage in the process of disbursement of funds.